IMF Staff Papers : Volume 49: Special Issue: IMF Annual Research Conference. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2002)
This paper reports for uncovered interest parity (UIP) using daily data for 23 developing and developed countries during the crisis-strewn 1990s. UIP is a classic topic of international finance, a critical building block of most theoretical models, and a dismal empirical failure. UIP states that the interest differential is, on average, equal to the ex post exchange rate change. UIP may work differently for countries in crisis, whose exchange and interest rates both display considerably more volatility. This volatility raises the stakes for financial markets and central banks; it also may provide a more statistically powerful test for the UIP hypothesis. Policy-exploitable deviations from UIP are, therefore, a necessary condition for an interest rate defense. There is a considerable amount of heterogeneity in the results, which differ wildly by country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet